Made to serve: a model of the operations practices and technologies that deliver servitization - Baines, Tim S.; Lightfoot, Howard (Cranfield University Press, 2013)
This paper explores how successfully servitised manufacturers deliver advanced services and proposes a model that describes how they configure their operations. A case study methodology is applied across four manufacturing organisations successful in delivering advanced services. A descriptive model is then formed based around six popular technologies and practices.
Keywords: Servitization; Product-service systems; case study